The Influence of Infection and Colonization on Outcomes in Inpatients With COVID-19: Are We Forgetting Something? - Alfonso-Sanchez, Jose Luis; Agurto-Ramirez, Adriana; Chong-Valbuena, María A.; De-Jesús-María, Isabel; Julián-Paches, Paula; López-Cerrillo, Luis; Piedrahita-Valdés, Hilary; Giménez-Azagra, Martina; Martín-Moreno, José María (Frontiers in Public Health, 2021)
The covid-19 epidemic has been a great challenge to health systems and especially hospitals. A prospective observational epidemiological study was planned as of February 26, 2020 in a tertiary hospital in the Valencia region. The total number of patients followed up with complete information during the first year was 2,448. Among other variables, the comorbidities of the patients were collected (and grouped in the Charson index), the stay in the ICU, the co-infections and the colonizations. Data on nosocomial infections due to said virus were also collected. The median days from the onset of symptoms to diagnosis were 4 + 4.6, while an additional 4.4 days had to pass for the patients to be admitted to the ICU. The factors associated with a higher risk of death were those with coinfection, especially with candida auris (OR: 4.6), a situation that also occurred in the ICU (OR: 3.18). Charlson Index comorbidity and candida auris colonization were also very important both in general hospitalization and in the ICU.